2017
DOI: 10.3389/fimmu.2017.00495
|View full text |Cite
|
Sign up to set email alerts
|

Divergent Expression of CXCR5 and CCR5 on CD4+ T Cells and the Paradoxical Accumulation of T Follicular Helper Cells during HIV Infection

Abstract: Viral infection sets in motion a cascade of immune responses, including both CXCR5+CD4+ T follicular helper (Tfh) cells that regulate humoral immunity and CCR5+CD4+ T cells that mediate cell-mediated immunity. In peripheral blood mononuclear cells, the majority of memory CD4+ T cells appear to fall into either of these two lineages, CCR5−CXCR5+ or CCR5+CXCR5−. Very high titers of anti-HIV IgG antibodies are a hallmark of infection, strongly suggesting that there is significant HIV-specific CD4+ T cell help to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 110 publications
0
13
0
1
Order By: Relevance
“…Alternatively, we have proposed that CXCR5+CCR5+ CD4+ T cells migrating towards germinal centers may be an intermediate or precursor stage for bona fide Tfh cells restricted to germinal centers, and CCR5 may be downregulated once they reach this target destination [130]. This could explain why Tfh cells in germinal centers may be infected with SIV/HIV, despite the absence of CCR5 expression [133]. In SIV-infected macaques and HIV-infected humans, Tfh cells abnormally accumulate in germinal centers, and many of these are productively, and latently infected [46, 125, 133].…”
Section: Specific Cd4+ T Cells Depleted In Siv/hiv Infectionmentioning
confidence: 99%
“…Alternatively, we have proposed that CXCR5+CCR5+ CD4+ T cells migrating towards germinal centers may be an intermediate or precursor stage for bona fide Tfh cells restricted to germinal centers, and CCR5 may be downregulated once they reach this target destination [130]. This could explain why Tfh cells in germinal centers may be infected with SIV/HIV, despite the absence of CCR5 expression [133]. In SIV-infected macaques and HIV-infected humans, Tfh cells abnormally accumulate in germinal centers, and many of these are productively, and latently infected [46, 125, 133].…”
Section: Specific Cd4+ T Cells Depleted In Siv/hiv Infectionmentioning
confidence: 99%
“…However, mechanisms by which these cells get infected remain unclear. T FH express very little CCR5 and in macaque studies, it has been shown that T FH lacking CCR5 cells can be infected in vivo with CCR5-tropic SIV ( 91 , 92 ). Infection of the T FH population by CCR-5 tropic viruses appears to be the result of infection of the pre-T FH cells that express CCR-5 ( 93 ).…”
Section: Key Cellular Players In the Clnmentioning
confidence: 99%
“…Tfh cell dysregulation leading to impaired B cell responses and ultimately humoral immune responses have also been reported in human immunodeficiency virus/simian immunodeficiency virus (HIV/SIV) [ 126 ]. Studies have shown that expanded Tfh cell populations harbour higher levels of HIV or SIV DNA compared to other CD4+ T cell subsets, can effectively support productive HIV infection and form a major viral reservoir [ 127 , 128 , 129 ]. Additionally, expansion of HIV-specific GC Tfh cells and c-Tfh cells have been observed in chronic infection and are associated with increased IL-21 secretion and polyclonal hypergammaglobulinemia [ 130 ].…”
Section: Utilisation Of C-tfh Cells To Study Disease Statesmentioning
confidence: 99%